Anticancer effect of phthalocyanine derivatives on colorectal cancer: in vitro and in vivo model - ÖZDEMİR, MÜCAHİT; YALÇIN, BAHATTİN (My University, 2022)
Colorectal cancer (CRC), also known as bowel cancer, colon cancer, or rectal cancer, develops cancer from the colon or rectum. Although 5-Fluorouracil (5-FU) is the primary antineoplastic used in treatment, its low treatment efficiency has led to the search for new agents. Phthalocyanines are aromatic macrocycles that contain four iso-indoline units connected by four nitrogen atoms. Phthalocyanines Derivatives (PD) gradually started to gain importance as anticancer agents. Our study aims to investigate the in vitro and in vivo anticancer effects of PD and 5-FU combinations on CRC. Cytotoxicity, genotoxicity, apoptosis, i-ROS, glutathione, calcium, and mitochondrial membrane potential were measured in LoVo and CCD18Co cells. Cells were given to nude mice by the xenograft method. After four weeks of single and combination therapy, tumor size was measured by in vivo imaging system (IVIS) and caliper. It was examined biochemically and histopathologically in related serum, tissues, and tumors. Combination treatment in vitro dose-dependently increased cytotoxicity, iROS, genotoxicity, apoptosis, and calcium significantly compared to a single treatment (p<0.001). DNA damage and apoptosis were induced higher in combined treatment than single treatment and increased statistically significantly (p<0.001). It was found that it decreased glutathione and MMP levels statistically (p<0.01; p<0.001). In all results of in vitro studies, PD affected cancer cells more than healthy cells. Combination treatment in vivo was found to reduce tumor size and density by a minimum of 66% at 30 days compared to a single treatment. Our results showed that PD has different anticancer properties in vivo and in vitro. The combined use of PD and 5-FU may be an option for routine colorectal cancer treatment.
Keywords: Phthalocyanine Derivatives; colorectal cancer; in vitro and in vivo cancer model